Influence of cadmium and arbuscular mycorrhizae on growth and chlorophyll content in Theobroma cacao and Theobroma grandiflorum Plants - Vallejos Torres, Geomar (2026)
Inoculation of arbuscular mycorrhizal fungi (AMF) has important benefits, not only for plant growth but also for reducing Cd absorption in Theobroma plants. This study aimed to investigate the influence of cadmium (Cd) and arbuscular mycorrhizae (AM) on growth and chlorophyll content (CC) in Theobroma plants. This experiment had a 3 × 2 × 2 factorial design with species of Theobroma cacao and Theobroma grandiflorum, AMF inoculation (mycorrhizal control and AMF inoculation), and Cd addition (0, 1, and 3 mg kg⁻¹), arranged in a completely randomized design with three repetitions. The AMF inoculum consisted of applying 1500 units to each seedling. The results showed that the Cd content decreased in the stems with AMF treatment for T. cacao as well as in the soil, showing significant differences in both variables. However, a reduction of Cd could also be observed in T. grandiflorum stems without significant differences with Cd in the soil. The height, diameter, root biomass, and leaf area (LA) of the Theobroma plants increased in most of the treatments studied in comparison with treatments that received Cd, as did CC. The AMFs inoculated into Theobroma plants induced higher CC in leaves. Likewise, T. cacao presented a higher value in morphology and a lower Cd concentration in soil and shoots.